2023
DOI: 10.1007/s12687-023-00646-y
|View full text |Cite
|
Sign up to set email alerts
|

Never “totally prepared”: Support groups on helping families prepare for a child with a genetic condition

Abstract: A rapid increase in the reach and breadth of prenatal genetic screening and testing has led to an expanding need for prenatal support of families receiving this genetic information. As part of a larger study investigating prenatal preparation for a child with a genetic condition, we interviewed representatives of patient advocacy groups (PAGs) who support parents postdiagnosis. Groups supporting families with Down syndrome were often local or regional, while other groups were often national or international in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Findings from this study revealed that after controlling for all the covariates and accounting for IFC, all of the predictor variables for associated with DS (Ajuwon, 2012;Braga et al, 2020;Choi, 2015;Choi & Yoo, 2015;Choi & van Riper, 2020;Clark et al, 2020;Craig et al, 2023: Geok et al, 2013Hsiao, 2014;Hsiao & van Riper, 2011;Huiracocha et al, 2017;Lanfranchi & Vianello, 2012;Thomas, 2021), As far as limitations of this study, the study included families of children with DS ranging in age from 1 to 50 years; however, the mean age for children with DS was 10.1, so the sample was skewed toward families of children. Second, while fathers from all 12 countries participated, they were under-represented.…”
Section: Analysesmentioning
confidence: 87%
See 1 more Smart Citation
“…Findings from this study revealed that after controlling for all the covariates and accounting for IFC, all of the predictor variables for associated with DS (Ajuwon, 2012;Braga et al, 2020;Choi, 2015;Choi & Yoo, 2015;Choi & van Riper, 2020;Clark et al, 2020;Craig et al, 2023: Geok et al, 2013Hsiao, 2014;Hsiao & van Riper, 2011;Huiracocha et al, 2017;Lanfranchi & Vianello, 2012;Thomas, 2021), As far as limitations of this study, the study included families of children with DS ranging in age from 1 to 50 years; however, the mean age for children with DS was 10.1, so the sample was skewed toward families of children. Second, while fathers from all 12 countries participated, they were under-represented.…”
Section: Analysesmentioning
confidence: 87%
“…There is also greater awareness of factors that can influence a family's ability to adapt. These factors include, but are not limited to, parent and family system variables (e.g., parental health, parental depression, family demands, and family resources), sociocultural variables (e.g., family income, educational level of the parents, access to resources, cultural values, religion and societal views about disability) and social processes (e.g., family decision making surrounding the DS diagnosis, construction and maintenance of sustainable family routines, and family sense-making; Ajuwon, 2012;Braga et al, 2020;Choi, 2015;Choi & Yoo, 2015;Choi & van Riper, 2020;Clark et al, 2020;Craig et al, 2023: Geok et al, 2013Hsiao, 2014;Hsiao & van Riper, 2011;Huiracocha et al, 2017;Lanfranchi & Vianello, 2012;Thomas, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…These findings indicate that clinicians should routinely offer referral to peer support when managing women with a diagnosis of CMV infection during pregnancy. 34 The main strength of our study is the in-depth interviews performed using a focused sample of women with positive CMV serology during pregnancy. We had a range of pregnancy outcomes and reproductive choices in our cohort, ensuring that we had a breadth of participant experience.…”
Section: Subcategories Supporting Illustrative Quotesmentioning
confidence: 99%